Controlled 2-Frames in 2-Hilbert Spaces - Reddy, Gujjula (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
Controlled frames in Hilbert spaces and 2-frames in 2-Hilbert spaces are studied, some results on them are presented. The controlled 2-frames in 2-Hilbert spaces is introduced. Some results on controlled 2-frames are established.